Perancangan Model Lean Manufacturing untuk Meningkatkan Key Performance Indicators Quality Assurance pada Perusahaan Penghasil Produk Kemasan Plastik - Rosi Theresia; Iveline Anne Marie; Nora Azm (JURNAL TEKNIK INDUSTRI, 2020)
Intisari— Menghadapi persaingan industri yang semakin ketat, perusahaan penghasil produk kemasan plastik berusaha meningkatkan daya saingnya dengan meningkatkan performansinya. Performansi perusahaan penghasil produk kemasan plastik dalam hal peningkatan value ke customer dapat diukur melalui key performance indicators bagian quality assurance. Pencapaian key performance indicators quality assurance perlu dibuat sebuah model yang tepat untuk meningkatkan key performance indicators quality assurance melalui pendekatan lean manufacturing Penelitian ini bertujuan untuk merancang model lean manufacturing untuk meningkatkan key performance indicators quality assurance. Tahapan awal dimulai dari studi literatur lean manufacturing tools dan survei ke berbagai perusahaan kemasan plastik sehingga diperoleh data yang dibutuhkan dalam rancangan model. Rancangan model harus dilakukan validasi pada perusahaan penghasil produk kemasan plastik. Setiap model memberikan manfaat dan dapat digunakan untuk memecahkan masalah mengenai tidak tercapainya key performance indicators quality assurance. Hasil rancangan model terdiri dari sub model 1 (current key performance indicators quality assurance), sub model 2 (current defect customer complaint), sub model 3 (lean manufacturing tools ) dan sub model 4 (future total complaint, future reject retur, future repeat issue, future resolution time dan future key performance indicators quality assurance). Diharapkan rancangan model lean manufacturing dapat menjadi solusi bagi perusahaan penghasil produk kemasan plastik untuk meningkatkan key performance indicators quality assurance.Abstract— Facing increasingly fierce industry competition, companies that produce plastic packaging products try to improve their competitiveness by increasing their performance. The performance of companies producing plastic packaging products in terms of increasing value to customers can be measured through the key performance indicators of the quality assurance section. Achievement of key performance indicators of quality assurance needs to be made an appropriate model to improve key performance indicators of quality assurance through a lean manufacturing approach. This study aims to design a lean manufacturing model to achieve key performance indicators of quality assurance. The initial stage starts from the study of lean manufacturing tools literature and surveys to various plastic packaging companies in order to obtain the data needed in the design of the model. The design of the model must be validated at the companies producing plastic packaging products. Each model provides benefits and can be used to solve problems regarding not achieving key performance indicators of quality assurance. The results of the model design consist of sub model 1 (current key performance indicators quality assurance), sub model 2 (current defect customer complaints), sub model 3 (lean manufacturing tools) and sub model 4 (future total complaints, future reject returns, future repeat issue, future resolution time and future key performance indicators quality assurance). It is hoped that the design of lean manufacturing models can be a solution for companies producing plastic packaging products to achieve key performance indicators of quality assurance.